2010
DOI: 10.1210/en.2010-0378
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen-Induced Apoptosis of Breast Epithelial Cells Is Blocked by NO/cGMP and Mediated by Extranuclear Estrogen Receptors

Abstract: Estrogen action, via both nuclear and extranuclear estrogen receptors (ERs), induces a variety of cellular signals that are prosurvival or proliferative, whereas nitric oxide (NO) can inhibit apoptosis via caspase S-nitrosylation and via activation of soluble guanylyl cyclase to produce cGMP. The action of 17β-estradiol (E(2)) at ER is known to elicit NO signaling via activation of NO synthase (NOS) in many tissues. The MCF-10A nontumorigenic, mammary epithelial cell line is genetically stable and insensitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 85 publications
1
13
0
Order By: Relevance
“…3-[4, 5-Dimethylthiazol-2-yl]-2, 5-diphenyltetrazolium bromide (MTT) assay was performed to measure cell viability as described previously (32). …”
Section: Methodsmentioning
confidence: 99%
“…3-[4, 5-Dimethylthiazol-2-yl]-2, 5-diphenyltetrazolium bromide (MTT) assay was performed to measure cell viability as described previously (32). …”
Section: Methodsmentioning
confidence: 99%
“…MCF-10A cells are formally considered as ER(-), since estrogen does not induce proliferation; however, the presence of ER protein and mRNA has been determined in MCF-10A cells (37-41). Since the primary biological target of SERMs is ER, it was essential to determine if classical ER signaling via these proximal receptors was causal in modulation of oxidative metabolism to produce catechol estrogens.…”
Section: Resultsmentioning
confidence: 99%
“…Most notably, several studies have shown that activation of nitric oxide synthase (NOS) and the subsequent production of NO, an activator of sGC, promotes proliferation, invasion, and metastasis in various models of breast cancer [42][43][44][45]. Additionally, NOS expression in triple negative breast cancer correlates with poor prognosis [45].…”
Section: Cgmp Signaling In Breast Cancermentioning
confidence: 99%